How libraries create value and help diminishing the digital divide - Maceviciute, Elena (Qualitative and Quantitative Methods in Libraries, 2019)
The paper addresses the issue of library value through two aspects: first, how libraries add value to societies and communities in a very general way; second, how libraries help to create equal and inclusive communities and societies. Five functions of library system and libraries are identified in the library literature, all of which help to create a more equal and just society in one way or another. The more concrete ways, in which libraries address the issues of social inequalities, are illustrated by examples of Lithuanian library activities.